Cloning and characterisation of type I interferon receptor 1 in orange-spotted grouper (Epinephelus coioides) for response to nodavirus infection. Issue 101 (June 2020) - Tang, Zhi Zhuang; Wang, Ting-Yu; Chen, Young-Mao; Chen, Tzong-Yueh
Abstract: Grouper is known as a highly economical teleost species in the Asian aquaculture industry; however, intensive culture activities easily cause disease outbreak, especially viral disease. For the prevention of viral outbreaks, interferon (IFN) is among the major defence systems being studied in different species. Fish type I IFNs are known to possess antiviral properties similar to mammalian type I IFNs. In order to stimulate antiviral function, IFN will bind to its cognate receptor, the type I interferon receptor (IFNAR), composed of heterodimeric receptor subunits known as IFNAR1 and IFNΑR2. The binding of type I interferon to receptors assists in the transduction of signals from the external to internal environments of cells to activate biological responses. In order to study the function of IFN, we first need to understand IFN receptors. In this study, we cloned and identified IFNAR1 in orange-spotted grouper (osgIFNAR1) and noted the up-regulated mRNA expression of the receptor and downstream effectors in the head kidney cells with cytokine treatment. The transcriptional expression of osgIFNAR1, which is characterised using polyinosinic-polycytidylic acid (poly[I:C]) and lipopolysaccharide (LPS) treatments, indicated the involvement of osgIFNAR1 in the immune response of grouper. The subcellular localisation of osgIFNAR1 demonstrated scattering across the grouper cell. Viral infection showed the negative feedback regulation of osgIFNAR1 in grouper larvae. Further loss of function of IFNAR1 showed a decreased expression of the virus. This study reported the identification of osgIFNAR1 and characterisation of receptor sensitivity towards immunostimulants, cytokine response, and viral challenge in the interferon pathway of orange-spotted grouper and possible different role of the receptor in viral production. Together, these results provide a frontline report of the potential function of osgIFNAR1 in the innate immunity of teleost. Highlights: OsgIFNAR1 was majorly expressed in brain and gill. OsgIFNAR1 induced Mx expression. OsgIFNAR1 could help NNV production before turn on antiviral system.